The Role of Marketing in the Development and Popularization of Football - Esanov, Javlon (European Journal of Life Safety and Stability (2660-9630), 2024)
This article examines the significant role that marketing has played in the transformation of football from a regional sport to a global phenomenon. It delves into the key marketing strategies employed by clubs, leagues, and governing bodies to build brand identity, expand reach, promote player development, drive revenue, and foster positive social impact. The article concludes by highlighting the enduring influence of marketing on the sport's trajectory and its continued relevance in a rapidly evolving global landscape.